Recent advances in biotechnological production of 2-phenylethanol - Hua, Dongliang; Xu, Ping (Biotechnology advances, 2011)
2-Phenylethanol (2-PE) is an important aromatic alcohol with a rose-like fragrance. It has been widely applied in the cosmetic, perfume, and food industries and is mainly produced by chemical synthesis. An alternative method for the production of natural flavors and fragrances is the microbial transformation process, which is attracting increasing attention because it is an environmentally friendly process and the products are considered “natural”. The production of 2-PE from L-phenylalanine by biotransformation is possible through the Ehrlich pathway and considerable progress has been made in the development of this process. The present report reviews recent advances in biotechnological production of 2-PE, with emphasis on the strategies used to increase production and the applications of in situ product removal techniques. Future research should focus on product scale-up and product recovery processes for the industrialization of microbial processes.